2007
DOI: 10.1111/j.1365-2354.2007.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Organization-based performance measures of cancer care quality: core measure development for breast cancer in Taiwan

Abstract: The purpose of the study was to develop organization-based core performance measures (CPMs) for breast cancer patients treated in hospitals that participated in cancer quality improvement programmes in Taiwan. CPMs were developed in three stages that included a preparation, a consensus building stage, and two stages of stakeholder feedback. Three criteria and seven subcriteria were applied in the development process. Indicators listed in a Delphi questionnaire were based on a literature search, indicators deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 48 publications
0
25
1
1
Order By: Relevance
“…The panel represented hospital domains of marketing (managers who conduct quarterly patient satisfaction surveys), clinical quality assurance (clinicians, physician, and nurse managers who monitor quality care indicators), human resource management (staff and managers who conduct annual staff satisfaction surveys), and budget and planning (financial managers furnishing financial reports). As per recommendation of other studies (Chung et al, 2008) it was ensured that experts committed time and involvement until the process was complete.…”
Section: Methodsmentioning
confidence: 99%
“…The panel represented hospital domains of marketing (managers who conduct quarterly patient satisfaction surveys), clinical quality assurance (clinicians, physician, and nurse managers who monitor quality care indicators), human resource management (staff and managers who conduct annual staff satisfaction surveys), and budget and planning (financial managers furnishing financial reports). As per recommendation of other studies (Chung et al, 2008) it was ensured that experts committed time and involvement until the process was complete.…”
Section: Methodsmentioning
confidence: 99%
“…Taiwan Cancer Database was initiated in 2003 by the Bureau of Health Promotion, Department of Health, Taiwan. A joint breast cancer treatment committee at each participant hospital had established a prospectively collected database (27). Thirtytwo hospitals including NTUH had participated in this program by 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a German population-based study found that 91% of patients with invasive breast cancer received radiotherapy following conservative surgery (6). Further, Taiwan recently adopted receipt of breast radiotherapy as a core performance measure for their nationwide cancer quality improvement program and may consider integration of this measure into a payfor-performance program, although baseline compliance with this measure has not yet been reported (7). As more countries look to measure the quality of their breast cancer programs and further seek to link quality of care to reimbursement, the data in this study will serve as a benchmark to define radiotherapy utilization rates that are achievable in the community practice setting.…”
Section: Discussionmentioning
confidence: 98%
“…The first step in evaluating the potential impact of PQRI is to determine baseline compliance with PQRI measures before their implementation. Further, quantification of compliance with this quality indicator in the U.S. population will serve as a benchmark for other countries with different health care systems who seek to measure and improve quality of breast cancer care (5)(6)(7). Therefore, we determined baseline utilization of radiotherapy before implementation of PQRI in a cohort of Medicare beneficiaries for whom breast radiotherapy is recommended.…”
Section: Introductionmentioning
confidence: 99%